A Model of Economic Empowerment of Conflict Victims Through Agrarian Reform Program in Poverty Reduction and Strengthening of Peace in Aceh - Zahari Zahari; Dedy Syahputra; Joelman Subaidi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze: (1) A model of economic empowerment for conflict-affected communities through the Agrarian Reform program in alleviating poverty and strengthening Aceh's peace. (2) analyzing the Agrarian Reform strategic program in the context of poverty alleviation and strengthening peace in Aceh. In order to achieve the aims and objectives of this research scheme, a constructivism paradigm is used with a qualitative research method approach with the stages of the research method: (1) Research preparation, research observation, research data collection, analysis and presentation of research data, research conclusion drawing, research site review, preparation final research report preparation of journals, preparation of research results recommendations. As well as carrying out Focus group discussions on the formulation of research recommendations as outputs requested in the basic research scheme in the development of national competence for novice research lecturers. The research outputs that are attempted in this study are: (1) the results of this research will be published in national and/or international journals. (2) the results of this study will be used as a reference in the form of a monograph book for ISBN publishers. (3) The level of maturity or readiness for this research will be conveyed to the local government and related institutions so that it can become a joint guideline for the implementation of the economic empowerment model for conflict-affected communities in alleviating poverty, unemployment and strengthening Aceh peace.